1996
DOI: 10.1152/jn.1996.76.1.492
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar ataxia: abnormal control of interaction torques across multiple joints

Abstract: 1. We studied seven subjects with cerebellar lesions and seven control subjects as they made reaching movements in the sagittal plane to a target directly in front of them. Reaches were made under three different conditions: 1) "slow-accurate," 2) "fast-accurate," and 3) "fast as possible." All subjects were videotaped moving in a sagittal plane with markers on the index finger, wrist, elbow, and shoulder. Marker positions were digitized and then used to calculate joint angles. For each of the shoulder, elbow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
333
2
12

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 529 publications
(367 citation statements)
references
References 29 publications
20
333
2
12
Order By: Relevance
“…It means that the movements were not segmented so as to minimize self-generated Coriolis torques incumbent on torso rotation. This finding may be contrasted with those from investigations of pathological populations: in particular, decomposition of elbow and shoulder joint motions [a strategy that reduces the interaction torques at the moving joint (Bastian et al 1996)] and transient locking of the elbow joint (Sainburg et al 1993) have been observed in slow reaching movements performed by cerebellar subjects and in "slicing" gestures performed by deafferented subjects, respectively.…”
Section: Sequencing Of Arm and Trunk Motioncontrasting
confidence: 71%
“…It means that the movements were not segmented so as to minimize self-generated Coriolis torques incumbent on torso rotation. This finding may be contrasted with those from investigations of pathological populations: in particular, decomposition of elbow and shoulder joint motions [a strategy that reduces the interaction torques at the moving joint (Bastian et al 1996)] and transient locking of the elbow joint (Sainburg et al 1993) have been observed in slow reaching movements performed by cerebellar subjects and in "slicing" gestures performed by deafferented subjects, respectively.…”
Section: Sequencing Of Arm and Trunk Motioncontrasting
confidence: 71%
“…Moreover, both populations exhibited shifts in activity during movements. Bastian et al (1996a) found that cerebellar subjects performing fast-reaching movements often generate inappropriate muscle torques relative to the dynamic interaction torques. The inability to produce muscle torques that compensate for the dynamic interaction torques appears to be an important cause of the de®cits shown by cerebellar subjects during reaching.…”
Section: Resultsmentioning
confidence: 99%
“…Functional imaging studies have identified the cerebellum in the regulation of velocity and extent of movement (Turner et al, 2003a). However, in these studies, interaction torques may have played a significant role, especially given that altered control of interaction torques underlies impaired multijoint reaching movements observed in cerebellar disease (Bastian et al, 1996). However, in the near isometric conditions of the present study, no such torques arise, which identifies the cerebellar activation with pure force control, although this may have included monitoring of force either through efferent or afferent signals.…”
Section: Discussionmentioning
confidence: 99%